Chinese airline competitiveness evaluation based on extended binary relative evaluation(BRE) model - Wu, Chong; Wang, Xin; Zhang, Xinying; Li, Yongli; O’Brien, Brad (Journal of Business Economics and Management, 2013)
In order to eliminate the impact of the sample's objective merits on the evaluation results, this research built a two-stage model of Chinese airline competitiveness evaluation to reflect the subjective management and performance. In the first stage, Analytic Hierarchy Process (AHP) and Factor Analysis (FA) models were used to analyze the data from 2008 to 2009. In the second stage, two kinds of comprehensive evaluation indexes in 2008 were taken as the reference index set, and two kinds of comprehensive evaluation indexes in 2009 as the current index set. The four sets of data were calculated with the Group Decision-making Model Based on Data Envelopment Analysis (DEA) with Restraint Cone. This paper has (1) enriched the theory of airline competitiveness,(2) built a more scientific and comprehensive evaluation index system of airlines’ competitiveness, (3) constructed a competitiveness evaluation model based on BRE, and (4) conducted an empirical study of the improved model based on the 2008 and 2009 data from 15 Chinese airlines. The ranking results of the proposed method, theory and model coincide with the real conditions of the airline market demonstrating that our evaluation of airline competitiveness based on BRE is accurate, reliable and objective.